Anti-proteolytic activity of Ganoderma lucidum methanol extract against Pseudomonas aeruginosa - Nessma Ahmed El Zawawy; Sameh Samir Ali (Journal of Infection in Developing Countries)
Introduction: Protease enzyme is considered one of the most serious virulence factors produced by extended-spectrum β-lactamase-producing and multidrug-resistant Pseudomonas aeruginosa (ESβLMDRPA) clinical isolates. Methodology: The antibacterial activity of methanol extract of Ganoderma lucidum fruiting bodies was tested against a protease-producing ESβLMDRPA clinical isolate, showing its mode of action. Results: The extract showed high antibacterial activity. Its effect on purified protease indicated a reversible non-competitive protease inhibition (kis= 0.45 mg/mL). Conclusions: The G. lucidum extract could be a promising anti-proteolytic active against ESβLMDRPA. It may form a primary platform for further phytochemical studies and development of new drugs for therapy of skin burn infections.